Critical analysis of the labeling of commercialized foods (Research, Society and Development, 2020)
The information presented on food labels must be easy to understand and follow the criteria of national laws for better understanding of the food components. The objective of the study was to carry out a critical analysis of the information contained on labels of food available for sale and, compare them with the criteria established by Brazilian legislation. The observational study was carried out with 198 industrialized food labels available for sale in two supermarket chains, selected for convenience, in the city of Curitiba, Paraná. The product labels were photographed during the four visits to the supermarkets and were evaluated by means of an evaluation script composed by 64 items distributed in 23 categories regarding the criteria of the food labeling legislation. No label was found to be totally adequate in relation to the criteria of Brazilian legislation on food labeling. The label for sliced bread and jams were the least suitable, both with 92%. The categories with the highest number of irregularities were Lactose (54%), followed by Identification of origin (71%), Lot identification (79%), Food allergies (91%), Portion (96%), Shelf Life (97%) and  List of ingredients (98%). The presence of inadequate information on the labels of commercialized foods shows the need for greater commitment from manufacturers in their preparation. In addition, more effective enforcement by the competent authorities is necessary, to the benefit of the consumer's health.